PARENTAL AND NON-PARENTAL FIGURES OF ATTACHMENT AS PREDICTORS OF AFFECTIVE STYLES (Heritage, 2022)
Emotional regulation is one of the components of emotional intelligence that is very important for the development of the person and the quality of life in adulthood. Growing up, in a relationship with family, then with peers and finally with partners, we learn to regulate our emotional experiences and build characteristic affective styles. The aim of this paper is to examine whether there is an interdependence of figures of attachment in the prediction of affective styles in a sample of young adult girls who are currently in a partnership and those who are not (264 respondents). The instruments used were: Questionnaire for assessing partner, friend and family attachment – three versions (Kamenov, Jelić 2003). This questionnaire is a revised Croatian version of the ECR (Experience in Close Relationship Questionnaire) questionnaire (Brennan, Clark, Shaver 1998) and the ASQ Affective Style Questionnaire (Hofmann, Kashdan 2010). The connection between affective styles and attachment for all three examined figures was confirmed, as well as the predictive power of some dimensions of attachment in the explanation of affective styles. The initial hypotheses of this paper are only partially confirmed, but the results indicate important theoretical and practical implications that could be supplemented in future work. Attachment is obviously an important part in the space of emotion regulation, but it seems that the correlation is not direct and that there is an influence of many personal and situational variables that need to be researched in future.
Keywords: attachment, affective styles, parents, peers, friends, partners